2023
DOI: 10.1002/mus.27804
|View full text |Cite
|
Sign up to set email alerts
|

Risdiplam in non‐sitter patients aged 16 years and older with 5q spinal muscular atrophy

Abstract: Introduction/Aims Risdiplam has been approved for the treatment of patients with 5q spinal muscular atrophy (SMA), but data from type 2 non‐sitter patients are lacking. In this study we describe our experience regarding the use of risdiplam in a series of type 2 non‐sitter patients. Methods Type 2 SMA patients over 16 years of age were administered risdiplam through the expanded access program (NCT04256265). Patients were followed‐up with a battery of scales and clinical measures. Results Six non‐sitter patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Contrary to that, Ñungo Garzón et al reported no clinically meaningful deteriorations in RULM (worsening of RULM score ≥ 2 vs. baseline) during their 12 months follow-up period of six SMA type 2 patients [17]. A possible explanation for this might be a oor effect in their study as half of the patients scored 0 for their baseline RULM assessment [17]. McCluskey et al reported clinically meaningful improvement in RULM scores in two patients and stabilization in the other three (n = 6, one patient lost to follow-up) [16].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Contrary to that, Ñungo Garzón et al reported no clinically meaningful deteriorations in RULM (worsening of RULM score ≥ 2 vs. baseline) during their 12 months follow-up period of six SMA type 2 patients [17]. A possible explanation for this might be a oor effect in their study as half of the patients scored 0 for their baseline RULM assessment [17]. McCluskey et al reported clinically meaningful improvement in RULM scores in two patients and stabilization in the other three (n = 6, one patient lost to follow-up) [16].…”
Section: Discussionmentioning
confidence: 83%
“…In the study of Ñungo Garzón et al, two patients had previously been treated with nusinersen. Out of them, one patient remained stable, while the other one showed clinically meaningful improvement (improvement of RULM score ≥ 2 vs. baseline) after 12 months of treatment [17].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, clinical characteristics are hererogeneously distributed and show a preponderance of severely diseased non‐sitters and sitters, restricting the applicability of our findings to this patient population. However, the patients studied here resemble the previously reported risdiplam‐treated patient cohorts [9, 23, 24]. The cohort assessing the course of disease prior to pharmacotherapy is imbalanced to some degree regarding symptom duration and a tendency towards less severely affected patients, possibly biasing comparative analyses.…”
Section: Discussionmentioning
confidence: 87%
“…Another aspect to highlight was the improvement in patient‐reported outcome measures in SMA which include physical function, mental health and cognition, fatigue, communication and speech, pain, and systemic issues 45 . Although not included as an outcome in our review due to the large number of variables, the observations of some of the included studies should be highlighted 32,35 . These studies in adults showed improvements in some participants' fatigue, cognition, overall strength, manual dexterity and strength, speech, well‐being, and quality of life.…”
Section: Discussionmentioning
confidence: 99%